Anal fistula plug vs rectal advancement flap for the treatment of complex cryptoglandular anal fistulas: a systematic review and meta‐analysis of studies with long‐term follow‐up. (21st December 2018) - Lin, H.; Jin, Z.; Zhu, Y.; Diao, M.; Hu, W.
Abstract: Aim: The aim was to compare the effectiveness of the anal fistula plug (AFP) with the rectal advancement flap (RAF) for complex cryptoglandular anal fistulas. Methods: We conducted a literature search to identify relevant available articles published without language restriction from Embase and PubMed databases and the Cochrane Library. Studies comparing outcomes with the AFP vs RAF for complex cryptoglandular anal fistulas were eligible for inclusion. Results: A total of 11 articles with 810 patients were included in this meta‐analysis. Four RCTs and one observational clinical study provided long‐term follow‐up. The pooled analysis of all 11 studies indicated that there was no significant difference between the AFP and RAF in terms of healing rate, recurrence rate and incidence of fistula complications. However, the pooled results of studies with long‐term follow‐up revealed that the RAF group had a significantly higher healing rate (OR 0.32, 95% CI 0.13, 0.78, P  = 0.01) and lower recurrence rate (OR 4.45, 95% CI 1.45, 13.65, P  = 0.009) than the AFP group. Conclusions: For the treatment of complex cryptoglandular anal fistulas, the RAF was superior to the AFP in terms of healing and recurrence rate after pooling of randomized controlled trials with long‐term follow‐up, even though a comparison based on the pooling of all studies showed no significant difference.